CALIBRATION OF A TABLETOP CONFOCAL MICROBEAM X-RAY FLUORESCENCE SPECTROMETER FOR A QUANTITATIVE DEPTH PROFILES EVALUATION - Prokeš, Radek; Trojek, Tomáš (Radiation protection dosimetry, 2019)
Confocal micro-beam X-ray fluorescence analysis (confocal micro-XRF) is a non-destructive analytical tool for investigation of sample composition that enables acquiring three-dimensionally resolved information. This work describes a calibration procedure of a laboratory confocal micro-XRF setup, which leads to determination of its characteristic parameters. The calibration is performed using a tabletop confocal micro-XRF spectrometer designed recently at the Czech Technical University in Prague. The calibration procedure performed within this work comprises the essential steps of the setup characterization: excitation spectrum calculation, experimental determination of energy-dependent confocal volume size and integral sensitivity and calculation of the spectrometer sensitivity function. The results of the setup calibration will be used for development of a procedure enabling quantitative evaluation of the measured depth profiles.
Keywords: rentgenové záření; algoritmy; Calibration; Humans; spektrometrie rentgenová emisní; fluorescence; Algorithms; X-Rays; kalibrace; Fluorescence; lidé; Spectrometry, X-Ray Emission